2018
DOI: 10.3389/fneur.2018.00719
|View full text |Cite
|
Sign up to set email alerts
|

Microvascular Parameters Help to Predict Stroke Risk in the Asian Diabetic Population in Taiwan: A Population Based Case-Control Study

Abstract: Intensive glycemic control has not shown consistent findings in stroke prevention for diabetes patients, particularly for those with microvascular complications. This case-control study evaluates the risks of stroke in Asian diabetic population with microvascular complications. From the insurance claims of Taiwan, we identified 67,426 type 2 diabetic mellitus (DM) patients with newly diagnosed stroke in 2000–2011 and 134,852 randomly selected controls with DM but without stroke, matched by sex, age, and number… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 41 publications
(51 reference statements)
0
3
0
Order By: Relevance
“…Wicke et al reported that higher aDSCI levels are correlated with a higher risk of stroke, supporting our assumption 22 . Moreover, Lo et al reported that the three variables in the aDSCI—neuropathy, nephropathy, and retinopathy—indicate a higher risk of hemorrhagic stroke (adjusted hazard ratio [aHR] = 4.12) and ischemic stroke (aHR = 2.64) 23 . In our study, patients with hypoglycemia were more likely to have a aDSCI score of 2 (27.10% vs 24.58%) and had higher frequencies of ischemic stroke (11.43% vs 6.75%) and hemorrhagic stroke (2.11% vs 1.84%) among the colchicine users (Appendix Tables 1 and 2 ).…”
Section: Methodsmentioning
confidence: 99%
“…Wicke et al reported that higher aDSCI levels are correlated with a higher risk of stroke, supporting our assumption 22 . Moreover, Lo et al reported that the three variables in the aDSCI—neuropathy, nephropathy, and retinopathy—indicate a higher risk of hemorrhagic stroke (adjusted hazard ratio [aHR] = 4.12) and ischemic stroke (aHR = 2.64) 23 . In our study, patients with hypoglycemia were more likely to have a aDSCI score of 2 (27.10% vs 24.58%) and had higher frequencies of ischemic stroke (11.43% vs 6.75%) and hemorrhagic stroke (2.11% vs 1.84%) among the colchicine users (Appendix Tables 1 and 2 ).…”
Section: Methodsmentioning
confidence: 99%
“…Patients with retinopathy had a 1.11–7.35 times higher risk of stroke [ 21 ]. Patients with cardiac autonomic neuropathy exhibited a 1.7–2.7 folds higher risk of stroke than those without cardiac autonomic neuropathy [ 8 , 10 , 27 , 28 ]. Our study showed that patients with microvascular disease demonstrated a significantly higher risk of stroke development than those without microvascular disease.…”
Section: Discussionmentioning
confidence: 99%
“…Diabetic neuropathy is a syndrome that includes somatic and autonomic neuropathy of the peripheral nervous system [ 4 , 29 ]. The plausible mechanisms to explain the intense association of neuropathy and stroke development are as follows: first, diabetic neuropathy may lead to the dysfunction of the parasympathetic and sympathetic innervation of cerebral vasculatures, resulting in the defective autoregulation of cerebral blood flow and render the brain vessels more vulnerable to injury and occlusion [ 10 , 27 , 28 ]. Second, neuropathy may cause unstable baroreflex and heart rhythms and favor atrial fibrillation with subsequent stroke development [ 28 ].…”
Section: Discussionmentioning
confidence: 99%